(3JaSjQ GdbQBfs - (3ebGJd Hf SdjeGf Hf HTjQ GdCROj, CHh GdMSf,J (B150 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ ShQI (B" (3eQje (B" s
(3BNQgG (B:s
(3hjfJgi HJaSjQ (B" (3Me GdSLOI (B" s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B317s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B29 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B459s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs